دور الإعلانات الدولية في توطيد القواعد الدستورية المقررة للحقوق والحريات - قوي, نور الهدى; روشو, خالد (University of Eloued جامعة الوادي, 2021)
لمـا كانـــت الإنســانـيـة مفـهومــا عالميـــــا لا تقيــــــده حـــــدودا، ولما كانت الحريــــة، ومـــا تشتمــــل عليــــــــــــه مــــن مكـونات مبدأ يقــف في وجــه تمــرد السـلـطة؛ كانت الإعـلانات الدولــية للحــقــوق قد شقت طريقها نحو تحقيق غايات سامــية، أثــرت إيجــابــا في عمـليـات وضــع الدســاتـيـر، وإنشاء مؤسسات جبلت على حماية الحقوق على الصعيد الوطني، وقد برزت مجموعة من العراقيل، من أمثال التعصب لمفهوم السيادة، وافتقار الإعلانات للإلزام، غير أنها لم تحد عن تحقيق الهدف العالمي، كالقضاء على مختلف أشكال الانتهاك، وإن لم تقضي عـليـه كـلـيـا لـكـنها قــد ســاهمــت في التــقــلــيص مــن زخــمها، فربــطت وجــود الدســتور بوجــود الحــقوق والحريات. Abstract: Since humanity is a universal concept that is not bound by borders, and since freedom, and what it includes from the components of a principle that stands in the face of the rebellion of power. The international declarations of rights have made their way towards achieving lofty goals, which have positively affected the processes of drafting constitutions, and the establishment of institutions that have bred to protect rights at the national level, and a number of obstacles emerged, such as intolerance of the concept of sovereignty, and the lack of binding declarations, but they did not hinder the achievement of the global goal, such as eliminating various forms of violation, although it did not eliminate it completely, but it contributed to reducing its momentum, linking the existence of the constitution to the existence of rights and freedoms. Key Words: constitutional; International declarations; Rights and Freedoms.
The Role of International Declarations in Consolidating Constitutional Rules of Rights and Freedoms
مقال
Keywords: الدستور ; الإعلانات الدولية ; الحقوق والحريات; constitutional ; International declarations ; Rights and Freedoms